Intra-amniotic sildenafil treatment improves lung blood flow and pulmonary hypertension in congenital diaphragmatic hernia rats - Yoshida, Shiho; Kreger, Alexander M.; Gittes, George K. (Frontiers in Bioengineering and Biotechnology, 2023)
Pulmonary hypertension associated with congenital diaphragmatic hernia (CDH) is a critical factor in determining prognosis. We propose that intra-amniotic sildenafil administration is an effective prenatal therapy for CDH-induced pulmonary hypertension. To assess the efficacy of this treatment, we administered sildenafil to nitrofen-induced congenital diaphragmatic hernia fetuses and control fetuses via an intra-amniotic injection after a laparotomy on the pregnant dam at either E13.5 or E15.5. Intra-amniotic sildenafil treatment attenuated peripheral vascular muscularization, enhanced pulmonary blood flow, and increased the ratio of pulmonary artery size to aortic size in congenital diaphragmatic hernia fetuses after both E13.5 and E15.5 treatments. E13.5-treated congenital diaphragmatic hernia fetuses showed a higher and more prolonged expression of cyclic guanosine monophosphate (cGMP)-dependent protein kinase and more production of vascular endothelial growth factor, resulting in a significant improvement in lung architecture. The E13.5-treated congenital diaphragmatic hernia fetuses also had an increase in lung weight-to-body weight ratio and an improved fetal survival. Intra-amniotic sildenafil treatment did not show any detectable negative effects in control fetuses. Intra-amniotic sildenafil treatment for rats attenuates CDH-induced pulmonary hypertension and enhanced peripheral pulmonary blood flow. Moreover, early intervention may be preferable to better accelerate lung development and improve prognosis. Direct sildenafil administration via an intra-amniotic injection may be a promising option in congenital diaphragmatic hernia prenatal therapy.